CORPORATE GOVERNANCE, FINANCIAL PERFORMANCE, AND FIRM VALUE: EVIDENCE FROM MANUFACTURING COMPANIES IN INDONESIA - Isnaina Azhuri; Fazya Nindita Gustifa; Maghfiratul Aini (CV. Adiba Aisha Amira, 2026)
This research seeks to examine the influence of Good Corporate Governance (GCG), Profitability, Leverage, and Firm Size on the Firm Value of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The GCG variable in this study is represented by Managerial Ownership, Institutional Ownership, Independent Commissioners, and Audit Committees. This research adopts a quantitative approach, utilizing secondary data sourced from company annual reports covering the 2021–2023 period. The sampling method applied is purposive sampling, which produced a total of 240 samples. IBM SPSS 26 software was used to perform multiple linear regression analysis on the collected data. The results indicated that individually, managerial ownership, profitability, and leverage had a significant and positive effect on firm value. On the other hand, institutional ownership, independent commissioners, and company size showed no significant effect on firm value. Nonetheless, collectively, the independent variables had a statistically significant effect on firm value.